2006
DOI: 10.1093/ptj/86.5.710
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of the Effectiveness of Physical Therapy Interventions for Temporomandibular Disorders

Abstract: Background and Purpose. The purpose of this qualitative systematic review was to assess the evidence concerning the effectiveness of physical therapy interventions in the management of temporomandibular disorders. Methods. A literature search of published and unpublished articles resulted in the retrieval of 36 potential articles. Results. Twelve studies met all selection criteria for inclusion in the review: 4 studies addressed the use of therapeutic exercise interventions, 2 studies examined the use of acupu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
158
1
19

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 302 publications
(198 citation statements)
references
References 46 publications
4
158
1
19
Order By: Relevance
“…Eight SRs evaluated various physical treatments in patients with TMD ( Table 2). Of these SRs, six assessed acupuncture (23,(29)(30)(31)(32), three jaw exercises (23,33,34), two manual therapy (33,34), and three various forms of electrical therapy (30,34). Three SRs reported that acupuncture was better than no treatment, four SRs that acupuncture and other therapies yielded similar results, and one SR that acupuncture and placebo treatment had similar results.…”
Section: Resultsmentioning
confidence: 99%
“…Eight SRs evaluated various physical treatments in patients with TMD ( Table 2). Of these SRs, six assessed acupuncture (23,(29)(30)(31)(32), three jaw exercises (23,33,34), two manual therapy (33,34), and three various forms of electrical therapy (30,34). Three SRs reported that acupuncture was better than no treatment, four SRs that acupuncture and other therapies yielded similar results, and one SR that acupuncture and placebo treatment had similar results.…”
Section: Resultsmentioning
confidence: 99%
“…Each study was assessed independently by the same two independent reviewers using a rating system originally developed by de Vet and colleagues (23) and has been used previously in systematic reviews in rehabilitation research (10, 24). Disagreements were resolved by discussion.…”
Section: Methodsmentioning
confidence: 99%
“…Rarely, surgical therapy is necessary. Overall, the evidence for all treatment modalities in TMD is very scarce [78][79][80][81][82].…”
Section: Facial Pain As Encountered By the Stomatologist And Dentistmentioning
confidence: 99%